IMPLEMENTASI PERATURAN BUPATI NOMOR 12 TAHUN 2007 TENTANG PENATAAN DAN PEMBERDAYAA PEDAGANG KAKI LIMA DI KECAMATATAN TUALANG KABUPATEN SIAK - Utama, Dio Alif; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Street vendors are economic activities that move in the informal sector that has negative and positive impacts. The Siak Regency Government is addressing the problem of street vendors selling street shoulder by implementing structuring and empowerment. At present the structuring has been carried out with solutions to build people's markets, in contrast to the empowerment of activities carried out unsustainably. The purpose of this study was to determine the Implementation of Regional Regulation Number 12 Year 2007 Concerning Arrangement and Empowerment of Street Vendors in Siak District and the inhibiting factors of structuring and empowering street vendors. This research uses the concept of policy implementation theory according to George C. Edward III in (Sujianto, 2008) which has indicators of Communication, Resources, Disposition, and Bureaucratic Structure. This research method uses a descriptive qualitative method with data collection techniques including: observation, interviews and documentation. Research informants were appointed through purposive sampling and snowball sampling techniques. The results showed that the implementation of the arrangement and empowerment of street vendors was not maximized so that traders were still selling in areas that were prohibited from trading. The inhibiting factors in the Implementation of Regulations on Structuring and Empowering Street Vendors are the socialization of policies, participation of street vendors and budgets. The government should be able to further optimize the implementation of regional regulations on the regulation and empowerment of street vendors with a more assertive and active effort in controlling and empowering.Keyword: Implementation, Management and Empowerment, Street Vendors